The addition of Daphnia magna and Ascorbic Acid to Angelfish Feed to Improve Its Growth and Immune Response (Pterophyllum scalare) - Titan Aji Wiratama; Dessy Amitha Kusumaningdyah; Anis Zubaidah; David Hermawan; Hany Handajani (Faculty of Fisheries and Marine Universitas Airlangga, 2021)
HighlightThe growth of angelfish which supplemented D. magna enriched ascorbic acid was identified and analyzedThe survival rate of angelfish after challenge test using A. hydrophylla was identified and analyzedThe composition of ascorbic acid in D. magna was analysed using iodometry titration test D. magna that has been added ascorbic acid was analyzedAbstractAngelfish (Pterophyllum scalare) is a tropical ornamental fish in freshwater with considerable potential in the global market and promising cultivation. However, it has a slow growth. The purpose of this research was to find the impact of giving feeding variations, namely D. magna that enriched ascorbic acid on improving the angelfish growth and its immune response. The research method used was Completely Randomized Design (CRD) using four treatments and three replications. The dosage of ascorbic acid consisted of 0 mg/L, 50 mg/L, 100 mg/L, and 150 mg/L. The fish was fed twice a day and applied with ad libitum. The result showed the addition of ascorbic acid had impacted its growth, and it produced SGR 2.393±0.003 %/day and challenge tests. The Survival Rate (SR) after challenge test was 79.99±1.000 %. In conclusion, the highest amount of growth and survival was treatment D (150 mg/L).